A marine traffic simulation system for hub ports - Huang, Shell Ying (2013)
Ensuring congestion-free marine traffic is crucial for hub ports in the world. For these hub ports, there has been increasing demand in marine transport. Therefore a capacity-assessment tool that models and simulates the navigational network, the traffic flows and complex navigational behaviors of vessels is needed. The simulation model presented in this paper is unique in the scale and complexity of the waterway networks covered, the flexibility in defining the traffic flow patterns, and the degree of accuracy demanded of navigational behaviors. As such, none of the existing models and simulation tools is adequate for assessing the waterway capacity. The model was calibrated based on detailed analysis of historical records and consultations with domain experts. The model was used in the study of several future scenarios of a hob port. The simulation system built has laid a useful foundation for planning future marine traffic for hub ports.